Dibromido{2-(morpholin-4-yl)-N- 1-(2-pyridyl)ethylidene ethanamine-kappa N-3,N ',N ''}cadmium - Gwaram, N.S.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
The Cd-II ion in the title compound, [CdBr2(C13H19N3O)], is five-coordinated by the N,N ',N ''-tridentate Schiff base ligand and two Br atoms in a distorted square-pyramidal geometry. In the crystal, intermolecular C-H center dot center dot center dot O and C-H center dot center dot center dot Br hydrogen bonds link adjacent molecules into layers parallel to the ab plane. An intramolecular C-H center dot center dot center dot Br interaction is also observed.